Intellectual property jurisdiction strategies : where to litigate unitary rights vs national rights in the EU - Larsen, Torsten Bjørn (Elgar intellectual property law and practice, 2017)
This timely and practical guide compares the jurisdictional advantages of litigating a national IP right with those of the corresponding European unitary IP right. The study offers IP practitioners a meticulous yet principled basis for their jurisdictional decisions and shows why it is advantageous for infringers to litigate based on a national IP right and rightholders to litigate based on a European unitary IP right. Key features include: - the first book to focus on jurisdiction strategies in intellectual property litigation - coverage of intellectual property and private international law - analysis of the latest case law of national courts and the European Court of Justice including, Case C-523/10, Wintersteiger and Case C-360/12, Coty Prestige - helpful diagrams and tables providing easy access to key information and decision points - a state-of-the-art overview of the relevant legal framework, including the Unified Patent Court Jurisdiction and the new European Union Trademark Regulation. Intellectual Property Jurisdiction Strategies is an essential resource for intellectual property practitioners throughout the EU. It will also appeal to advanced students and academics needing an up-to-date reference for research into intellectual property law and policy.